A Study on the perspective of students and faculty towards English as a Medium of Instruction - Alfaran, Fathia Hasan (2016)
This study examines students’ English language skills when they study in classes where the medium of instruction is English in UAE universities, regarding the proficiency of students’ language skills during the four years of study. The study examines the effect of English as a medium of instruction (EMI) on language proficiency of students and lecturers’ points of view. The findings of the research are used as a basis for recommendations to universities who use EMI with recommendations to improve students’ language proficiency. This research is conducted among students whose L1 is not English. In this study, the questionnaire and the interview results indicate that there are various perceptions between the instructors and the students regarding language ability, in addition to difficulties linked with using English as a medium of instruction. For the target population (the students), studying in English is not a problem, and they rank their level in all English language skills from good to excellent. However, lecturers do not find that students’ language ability satisfies their expectations as the students are studying using English as the environment of their learning. The lecturers believe that writing and listening are the weakest language skills of their students. In the lecturers’ opinion, there should be adjustments to the contents of English courses and assessment criteria to match the language ability of their students. This study suggests that to develop the learners’ English language skills, universities have to enhance students’ language proficiency through setting clear instructional goals and adapting support systems for lecturers, in addition to giving courses through the entire studying period ( 4 years) and not only in the preparation year.